The civil service : its role and relevance in the development process - Onosode, Gamaliel O.; Anambra State (Nigeria) (Enugu [Nigeria] : Government printer, Enugu ; Anambra State of Nigeria, 1988)
This article impinges on the cost and benefit of the civil service to government as employer and to the economy which its existence ought to service optimally.
nmn, 27/03/19
Loans
Keywords: Economic policy; Civil service - developmental role; Public service; Politics and government; Nigeria